CGRP measurements in human plasma – a methodological study - Meßlinger, Karl; Vogler, Birgit; Kuhn, Annette; Sertel-Nakajima, Julika; Frank, Florian; Broessner, Gregor (Cephalalgia, 2021)
Background: Calcitonin gene-related peptide plasma levels have frequently been determined as a biomarker for primary headaches. However, published data is often inconsistent resulting from different methods that are not precisely described in most studies. Methods: We applied a well-proven enzyme-linked immunosorbent assay to measure calcitonin gene-related peptide concentrations in human blood plasma, we modified parameters of plasma preparation and protein purification and used calcitonin gene-related peptide-free plasma for standard solutions, which are described in detail. Results: Calcitonin gene-related peptide levels are stable in plasma with peptidase inhibitors and after deep-freezing. Calcitonin gene-related peptide standard solutions based on synthetic intercellular fluid or pooled plasma with pre-absorbed calcitonin gene-related peptide influenced the measurements but yielded both comprehensible results. In a sample of 56 healthy subjects the calcitonin gene-related peptide plasma levels varied considerably from low (<50 pg/mL) to very high (>500 pg/mL) values. After a 12-hour exposure of these subjects to normobaric hypoxia the individual calcitonin gene-related peptide levels remained stable. Conclusion: Buffering with peptidase inhibitors and immediate freezing or processing of plasma samples is essential to achieve reliable measurements. Individuals show considerable differences and partly high calcitonin gene-related peptide plasma levels without detectable pathological reason. Thus plasma measurements are suited particularly to follow calcitonin gene-related peptide levels in longitudinal studies. The use of data for this study was approved by the Ethics Committee of the Medical University of Innsbruck (https://www.i-med.ac.at/ethikkommission/; EK Nr: 1242/2017).
CRIS-Team Scopus Importer:2021-07-30
Keywords: blood plasma; Calcitonin gene-related peptide; enzyme-linked immunosorbent assay; normobaric hypoxia